Case Report: Initial Evidence of Safety and Efficacy of High Definition-Transcranial Direct Current Stimulation in a Patient With Neuropathic Pain and Implanted Spinal Cord Stimulator - Choi Deblieck (Frontiers Media S.A., 2021)
Neuropathic pain (NP), often treatment-refractory, is one of the most debilitating conditions contributing to suffering and disability worldwide. Recently, non-invasive neuromodulation techniques, particularly repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) have emerged as potential therapeutic alternatives due to their ability to alter cortical excitability of neural circuits. However, the magnetic field induced in rTMS may be unsafe for patients with an implanted electrode in the head or neck area while tDCS poses no theoretical risk of injury to these patients. High definition (HD)-tDCS is a novel, more focal technique of tDCS and may be safer to the patient compared to the more diffuse stimulation of conventional tDCS. To our knowledge, no study has ever demonstrated the safety and/or feasibility of HD-tDCS in patients with spinal cord stimulation (SCS) devices using computational modeling of induced electrical fields. Furthermore, this study highlights the potential use of (HD-)tDCS as predictive tool for a positive response in chronic epidural motor cortex stimulation (MCS), especially in patients with an implanted device not suitable for rTMS. In a 54-year-old woman with an implanted spinal cord stimulation (SCS) system for another pain syndrome, HD-tDCS was initiated for refractory post-surgical inferior alveolar nerve neuropathy. She was submitted to 7 days of anodal HD-tDCS over the left motor cortex at 1.5 mA for 30 min. A notable decrease in pain perception was observed, lasting for approximately 5–6 h (Numeric Rating Score decreased from 8 to 4.34). No adverse events were reported. The stimulation parameters and clinical efficacy of the SCS system remained unchanged. Additionally, computational analysis indicated no meaningful alteration of current flow when considering a model with a SCS implant with respect to a model without implant. Regarding the positive therapeutic effect of HD-tDCS, the patient was selected for an epidural MCS trial and subsequent implantation, which showed short-term pain relief of 50–75%. Although one case does not demonstrate efficacy, tolerability, or safety to the novel intervention, it paves the way for better diagnosis and treatment for patients who are otherwise excluded from other non-invasive neuromodulation techniques, such as rTMS. A positive tDCS effect could be a potential biomarker for positive epidural MCS response in patients with an implanted stimulation device non-compatible with rTMS.